Financial Technology’s Impact on Financial Management in Startup Companies - Eka Sulfiana A; Muchriana Muchran (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to examine the influence of financial technology (fintech) on financial management in startup companies. Startups face various challenges such as limited financial resources, unstable cash flows, and difficulties in accessing capital. Fintech offers innovative solutions that automate financial processes, enhance transparency, and provide alternative financing options such as peer-to-peer lending and crowdfunding. This research employs a literature review method by analyzing various academic and industry publications from 2018 to 2023, as well as case studies of startups that have successfully implemented fintech. The findings indicate that fintech significantly improves efficiency, accuracy, and accessibility in startup financial management. However, challenges such as data security, regulatory uncertainty, and internal adaptation remain critical concerns. It is recommended that startups select fintech solutions tailored to their needs and enhance human resource competencies through training. Collaboration among regulators, fintech providers, and startups is also essential to create a supportive ecosystem. Overall, fintech acts as a key driver of digital transformation in startup financial management, supporting sustainable business growth and competitiveness.